Public Rental Flats as a Solution? Feasibility Study of Kebondalem Rusunawa for the Urban Poor - Martia, Vivi (Universitas Negeri Semarang, 2025)
This study aims to analyze the level of housing suitability in the Kebondalem Simple Rental Flats (Rusunawa), Kendal Regency, as one form of solution for providing housing for low-income people (MBR). The background of this study is based on the need for decent, safe, and affordable housing amidst the growth of urbanization and limited housing land. The approach used in this study is quantitative descriptive to obtain more comprehensive information. This study examines several aspects of housing suitability, including the physical condition of the building such as structure and cleanliness, the availability and function of public and social facilities, the rusunawa management system which includes management policies, maintenance, and security, and the level of resident satisfaction with comfort, privacy, and accessibility. The results of this study indicate that there are several aspects that meet the eligibility standards, but there are also aspects that still need to be improved, especially in terms of building maintenance, completeness of facilities, and management effectiveness. The results of this study are expected to be input for local governments, rusunawa managers, and related parties in formulating better policies and strategies for providing decent, sustainable housing that is in accordance with the needs of low-income people.